Toxic efect of DDT and endosulfan in white shrimp postlarvae Litopenaeus vannamei (Decapoda: Penaeidae) from Chiapas, Mexico. - Castro-Castro, Vicente (2005)
We analized acute toxicity in white shrimp (Litopenaeus vannamei) postlarvae exposed to two chlorinated pesticides, DDT and endosulfan, under laboratory conditions during 168 hours, with controlled temperature (29 ± 1°C), salinity (3 ±1‰) and pH (8 ± 1). Median lethal concentrations (LC50), “incipient” LC50, median lethal time (LT50) the “maximum acceptable concentration of the toxic compound” (MACT) and “the safety level” (SL) were determined. The concentration of the compounds at which organism growth was reduced by 5 and 50% (EC5 and EC50), as well as changes in oxygen consumption patterns were determined in the surviving postlarvae. They were very sensitive to both compounds and DDT was thrice as toxic as endosulfan. Growth rate decreased 50 % and 80 % with endosulfan and DDT, respectively, at the experimental pestice concentration. The low resistance of postlarvae to DDT and endosulfan suggests that additional inflow of these pesticides into the aquatic system could affect the rate of shrimp production in the area.